Companies income tax and petroleum profits tax in Nigeria - Ani, A. A. (Ibadan : Oxford University Press, 1978)
This book explain the historical background of company taxation in Nigeria
oo 24/01/2019
Loans
Keywords: Corporations; Petroleum; Excess profits tax